An Analysis on Students’ Writing Skill in Descriptive Text by Using Movie The School For Good And Evil By Paul Feig at Second Semester of Batanghari University - Mega, Mega; Ismiyati, Yanti; Silfia, Efa (JELT: Journal of English Language Teaching, 2025)
This research aimed to analyze students’ writing skills in descriptive text by using the movie The School for Good and Evil. The method was descriptive quantitative with 17 second-semester students of Batanghari University as the sample. Data were collected through a writing test in which students described one of the movie characters. The results showed that the average score was 81.47, categorized as excellent. Eleven students (64.71%) were in the excellent category and six students (35.29%) were in the good category. This shows that movies can effectively stimulate students to improve descriptive writing.